Special Exercises to Develop Speed Endurance, Passing and Shooting Skills for Young Handball Players - Ali Radhi Abdul Hussein; Nabeel Kadhim Hrebid (CV. FOUNDAE, 2023)
The importance of the research was represented in the preparation of special exercises to develop speed endurance for young handball players, as well as identifying the effect of special exercises in developing speed endurance, passing and shooting performance for handball players. As for the research problem, it was represented in the low level of physical attributes and skillful performance (passing and shooting) from time to time during matches or in their last minutes or in their extra times, if any. As the player becomes in a difficult situation and requires him to perform a high physical and skillful work in front of a low level of speed tolerance, which negatively affects the implementation of his duties at the required speed, especially the attack, which leads to not achieving good results in the match. Accordingly, the researchers set their goals in preparing special exercises to develop speed endurance for young players in handball to develop speed endurance among players. Where the researchers hypothesized that there is a positive effect of special exercises in developing speed endurance, passing and shooting performance for handball players. The researchers concluded that the special exercises were effective in developing speed endurance among the respondents. Which prompted them to recommend the necessity of benefiting from the special exercises in developing the speed endurance characteristic of the junior handball club players, as it is one of the basic physical characteristics in developing offensive skills in handball